Public service innovation process of smart kampung program at Banyuwangi - Choirul Saleh; Ibad, Syahrul; Mindarty, Lely Indah; Hariyono, Bambang Santoso (Faculty of Communications Science, Dr. Soetomo University, 2023)
This study aims to describe and analyse the process of public service innovation through the Smart Kampung Banyuwangi program. The emergence of various qualified public service innovations is the main indicator of responsiveness in community services. This research has a qualitative method study, based on the analysis of the public innovation process of